2013
DOI: 10.1038/nature12525
|View full text |Cite
|
Sign up to set email alerts
|

Key role of symbiotic dinitrogen fixation in tropical forest secondary succession

Abstract: Forests contribute a significant portion of the land carbon sink, but their ability to sequester CO2 may be constrained by nitrogen, a major plant-limiting nutrient. Many tropical forests possess tree species capable of fixing atmospheric dinitrogen (N2), but it is unclear whether this functional group can supply the nitrogen needed as forests recover from disturbance or previous land use, or expand in response to rising CO2 (refs 6, 8). Here we identify a powerful feedback mechanism in which N2 fixation can o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
380
7
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 324 publications
(423 citation statements)
references
References 36 publications
31
380
7
5
Order By: Relevance
“…CWMs of leaf N for both tree size classes increased during succession, which apparently contradicts the decrease in the CWM of A mass . Previous studies (Becknell and Powers 2014;Whitfeld et al 2014) also have reported either anomalous variation or increases in the CWM of leaf N, possibly due to an increase in the abundance of N-fixing species (Batterman et al 2013) or increases in soil pH. The expectation that leaf N will decrease during succession is predicated upon its positive correlation with A mass (Wright et al 2004), although recent studies have demonstrated that this relationship is also mediated by leaf structural attributes, density, and thickness, which comprise LMA (Poorter et al 2009;Shipley et al 2005Shipley et al , 2006.…”
Section: Successional Shifts In Functional Strategiesmentioning
confidence: 98%
“…CWMs of leaf N for both tree size classes increased during succession, which apparently contradicts the decrease in the CWM of A mass . Previous studies (Becknell and Powers 2014;Whitfeld et al 2014) also have reported either anomalous variation or increases in the CWM of leaf N, possibly due to an increase in the abundance of N-fixing species (Batterman et al 2013) or increases in soil pH. The expectation that leaf N will decrease during succession is predicated upon its positive correlation with A mass (Wright et al 2004), although recent studies have demonstrated that this relationship is also mediated by leaf structural attributes, density, and thickness, which comprise LMA (Poorter et al 2009;Shipley et al 2005Shipley et al , 2006.…”
Section: Successional Shifts In Functional Strategiesmentioning
confidence: 98%
“…Ecosystem Processes: Nitrogen Cycling N 2 fixation, N mineralization, and (de)nitrification are all regulated by the availability of N. Evidence from wet forests suggests that legumes down-regulate symbiotic N 2 fixation as soil N becomes more available through secondary succession (Batterman et al, 2013;Sullivan et al, 2014a). Similarly, rates of free-living N 2 fixation in soils and the forest floor may decrease with increasing N availability, as seen in wet forests of Puerto Rico (Cusack et al, 2009).…”
Section: Ecosystem Processes: Soil Carbon Dynamicsmentioning
confidence: 99%
“…Overall, wood δ 15 N was not different between dominant and regenerating trees, and no significant spatial trends were identified in regenerating trees, which suggests that dominant trees exhibit little influence over the N dynamics of nearby regenerating trees (Weber et al 2008). Prior to the establishment of dominance, both dominant and suppressed trees displayed to increased plant uptake of N and reduced N supply (Batterman et al 2013, Vitousek et al 1989). …”
Section: Forest Dynamicsmentioning
confidence: 99%